2014
DOI: 10.3109/01480545.2013.866139
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of crocin on diazinon induced vascular toxicity in subchronic exposure in rat aortaex-vivo

Abstract: DZN induced vascular toxicity which may be due to oxidative stress and not to a cholinergic mechanism. Crocin improved toxic effects of DZN via reducing lipid peroxidation and restoring altered contractile and relaxant responses in rat aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Moreover, the cardiovascular protective effects of crocin are considered to be closely associated with its antioxidant activity [1, 5, 11, 32, 33]. Additional research has also shown that biocompounds from saffron, including crocin, exert a hypotensive effect in normotensive and hypertensive states [1, 7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the cardiovascular protective effects of crocin are considered to be closely associated with its antioxidant activity [1, 5, 11, 32, 33]. Additional research has also shown that biocompounds from saffron, including crocin, exert a hypotensive effect in normotensive and hypertensive states [1, 7].…”
Section: Discussionmentioning
confidence: 99%
“…Crocin is one of the major pharmacologically bioactive constituents in saffron [1, 5, 32], and possesses protective effects against cardiovascular diseases [1, 3, 5-7, 33]. Moreover, the cardiovascular protective effects of crocin are considered to be closely associated with its antioxidant activity [1, 5, 11, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…It was also indicated that down regulation of eNOS expression as a result of oxidized low density lipoprotein (LDL) and increased NO production in bovine aortic endothelial cells (BAECs) were inhibited by crocetin (34). Result of another study showed that crocin could improve vascular toxic effects of diazinon by restoring altered contractile responses to PE and KCl and impaired relaxant responses to acetylcholine and sodium nitroprusside in rat aorta (35). Moreover, crocin restored the effects of sub chronic diazinon administration on systolic blood pressure in rats (36).…”
Section: Discussionmentioning
confidence: 99%
“…43 In a similar study based on rat models, it was concluded that crocin improves toxic effects of diazinon through decreasing lipid peroxidation and restoring altered contractile and relaxant responses in aorta. 44 The cardio-protective effect of saffron active constituents including crocin has been confirmed through regulation of oxidative stress. 45 The finding concluded that Crocus sativus perfused during electrolysis might trap radical oxygen species and significantly improve myocardial function.…”
Section: Nephrotoxicity Effectmentioning
confidence: 99%